Application of the Principles of Safe Hemodynamic Rearrangement to Reduce the Risk of Cerebral Arteriovenous Malformation Rupture during Curative Embolization using the Multimodal Approach - Panarin, Vyacheslav A.; Moskalev, Andrei; Gladkikh, Victor S.; Alshevskaya, Alina A.; Strelnikov, Nikolay; Berestov, Vadim; Krivoshapkin, Alexey L.; Orlov, Kirill Yu (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2025)
The grading system for arteriovenous malformations (AVMs) and the curative embolization principles for reducing the risks of AVM rupture caused by abrupt hemodynamic rearrangement have been modified using mathematical modeling methods. The objective of the study was to confirm the clinical effectiveness of these principles for reducing the rate of postoperative bleeding according to real-world data.A retrospective study employing a pooled database involving 532 patients was performed for groups matched by demographic, anatomical, and clinical characteristics using the PSM method: the group of patients treated with adherence to all the embolization principles (Principles group, n = 92) and the control group of patients treated with violation of at least one principle (Control group, n = 46). Each patient underwent 1–9 embolization stages. If needed, radiosurgery or microsurgery was used at the final stage. The therapy outcomes were assessed according to the rate of achieving 100% AVM obliteration at follow-up angiography, as well as morbidity, mortality, and perioperative complication rate.Patients in the Principles group had much higher safety parameters after multimodal embolization therapy; the rate of postoperative bleeding episodes was 9 (9.78%) versus 11 (23.91%) in the Control group (p = 0.039). Radicality levels of AVM nidus obliteration at the control visit were comparable in groups (85 (93.41%) versus 42 (95.45%), respectively, p > 0.999), while the rate of neurologic deficit progression (worsening by at least 2 mRS points) in the principles group was significantly lower (5 (5.43%) versus 9 (19.57%), p = 0.015).Endovascular embolization shows great potential as the main curative option for reducing the risk of postoperative bleeding due to changing the patient management strategy. Occluding a fistula (if it is present) at the first stage and reducing the degree of AVM obliteration per stage to 60% for large-sized malformations improve treatment safety without decreasing its radicality.
Keywords: AVM; brain arteriovenous malformation